2018
DOI: 10.3389/fendo.2018.00604
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Alternative Splicing as a Regulatory Mechanism for Kissr2 in Pejerrey Fish

Abstract: Kisspeptin receptors are G-Protein-Coupled Receptors that regulate GnRH synthesis and release in vertebrates. Here, we report the gene structure of two kisspeptin receptors (kissr2 and kissr3) in pejerrey fish. Genomic analysis exposed a gene structure with 5 exons and 4 introns for kissr2 and 6 exons and 5 introns for kissr3. Two alternative variants for both genes, named kissr2_v1 and _v2, and kissr3_v1 and v2, were revealed by gene expression analyses of several tissues. For both receptors, these variants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…However, kisspeptin transcripts and proteins are widely distributed in various brain areas and tissues of fish, but no clear roles have been associated with these extra brain kisspeptins. These tissues/organs, include the pituitary gland, the spinal cord, the intestine, the gonads, and the liver ( 62 65 ). The presence of kisspeptin in blood has been detected in mammals ( 66 ).…”
Section: Tissue Expression and Neuroanatomical Distribution Of The Ki...mentioning
confidence: 99%
See 3 more Smart Citations
“…However, kisspeptin transcripts and proteins are widely distributed in various brain areas and tissues of fish, but no clear roles have been associated with these extra brain kisspeptins. These tissues/organs, include the pituitary gland, the spinal cord, the intestine, the gonads, and the liver ( 62 65 ). The presence of kisspeptin in blood has been detected in mammals ( 66 ).…”
Section: Tissue Expression and Neuroanatomical Distribution Of The Ki...mentioning
confidence: 99%
“…It is important to mention that alternative splice variants are frequently observed in mammals when analyzing GPCR tissue distribution ( 67 ), and spliced variants of kisspeptin have also been detected in several teleosts. For example, the presence of alternative splice variants for kissr2 and/or kissr3 was observed in Senegalese sole ( 6 , 45 ), southern bluefin tuna, Thunnus maccoyii ( 68 ), yellowtail kingfish, Seriola lalandi ( 68 ), zebrafish ( 69 ), European eel ( 44 ) and pejerrey fish ( 65 ) through intron retention. Mechaly et al.…”
Section: Tissue Expression and Neuroanatomical Distribution Of The Ki...mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in goldfish, intraperitoneal injections of kiss1, but not kiss2, stimulated the release of LH in sexually mature females 102 . Also, it has been reported that kiss2 may have effects on food intake and growth function 88,96,115 . Furthermore, it can act as a link between food intake, energy homeostasis, and reproduction [116][117][118] .…”
Section: Kisspeptinmentioning
confidence: 99%